Analyzing Teacher’s Teaching Style in Teaching Descriptive Texts for Seventh Grade Students at SMP Negeri 37 Medan - Lubis, Syafitri Sari R.; Ariatna (Universitas Negeri Medan, 2024)
This study aimed to analyze teachers' teaching styles, the realization of teachers' teachingstyles in teaching descriptive text, and the reason teacher uses teaching styles in teachingdescriptive text at SMP Negeri 37 Medan. This research was conducted using descriptivequalitative design to find out the teaching styles used by the teacher through observationchecklist, video-recording, and interviewing the teacher. The result of this study is that theteacher dominantly used the facilitator teaching style, and the teacher realizes the teachingstyle by using all types but is more dominant in the facilitator style as there is moreinteraction between the teacher and students during the descriptive text lesson and thereason why the teacher used teaching style in teaching description text is that manystudents still lack of vocabulary and to know each student well enough as a guide toteaching effectively.Keywords: Teaching Style, Delegator, Descriptive Texts